Pricing and reimbursement of innovative pharmaceuticals in France and the new healthcare reform - Natz, Alexander; Campion, Marie-Geneviève (Farmeconomia. Health Economics and Therapeutic Pathways, 2012)
Over the last years, many cost-containment measures were implemented by the government leading to drastic price-cuts. New paradigms and healthcare models are emerging and health technology assessments are increasingly taken into consideration. France has the second biggest rank in terms of healthcare spending after the US. Pharmaceuticals represented around 19% of the budget of the Health Insurance funds in 2009. In France, innovative pharmaceuticals have been subject for a long-time to price-control and cost-containment measures. The present review provides a general description of the French health care system, analyzing the developments and changes by the recent French health care reform.